Cognitive impairment burden in older and younger adults across the kidney transplant care continuum. Issue 10 (3rd August 2021) - Chu, Nadia M.; Chen, Xiaomeng; Gross, Alden L.; Carlson, Michelle C.; Garonzik‐Wang, Jacqueline M.; Norman, Silas P.; Mathur, Aarti; Abidi, Maheen Z.; Brennan, Daniel C.; Segev, Dorry L.; McAdams‐DeMarco, Mara A.
Abstract: Background: Younger kidney transplant (KT) candidates and recipients may have cognitive impairment due to chronic diseases and reliance on dialysis. Methods: To quantify cognitive impairment burden by age across the KT care continuum, we leveraged a two‐center cohort study of 3854 KT candidates at evaluation, 1114 recipients at admission, and 405 recipients at 1‐year post‐KT with measured global cognitive performance (3MS) or executive function (Trail Making Test). We also estimated burden of severe cognitive impairment that affects functional dependence (activities of daily living [ADL] < 6 or instrumental activities of daily living [IADL] < 8). Results: Among KT candidates, global cognitive impairment (18–34 years: 11.1%; 35–49 years: 14.0%; 50–64 years: 19.5%; ≥65 years: 22.0%) and severe cognitive impairment burden (18–34 years: 1.1%; 35–49 years: 3.0%; 50–64 years: 6.2%; ≥65 years: 7.7%) increased linearly with age. Among KT recipients at admission, global cognitive impairment (18–34 years: 9.1%; 35–49 years: 6.1%; 50–64 years: 9.3%; ≥65 years: 15.7%) and severe cognitive impairment burden (18–34 years: 1.4%; 35–49 years: 1.4%; 50–64 years: 2.2%; ≥65 years: 4.6%) was lower. Despite lowest burden of cognitive impairment among KT recipients at 1‐year post‐KT across all ages (18–34 years: 1.7%; 35–49 years: 3.4%; 50–64 years: 4.3%; ≥65 years: 6.5%), many still exhibited severe cognitive impairment (18–34 years: .0%; 35–49 years: 1.9%; 50–64 years: 2.4%; ≥65 years: 3.5%). Conclusion: Findings were consistent for executive function impairment. While cognitive impairment increases with age, younger KT candidates have a high burden comparable to community‐dwelling older adults, with some potentially suffering from severe forms. Transplant centers should consider routinely screening patients during clinical care encounters regardless of age.